2002
DOI: 10.1071/sr01069
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of K-Ca-Mg ternary exchange from binary isotherms in volcanic soils using the Rothmund-Kornfeld approach

Abstract: The Gaines-Thomas formulation of the Rothmund-Kornfeld equation was used to predict the K-Ca-Mg exchange in variable surface charge soils. Binary and ternary equilibria were carried out at 25°C and at constant ionic strength of 0.050 mol/L. The selectivity sequence K > Ca > Mg was observed in binary isotherms. The experimental ternary isotherms are well described from binary data. When experimental v. calculated equivalent fractions were plotted, slopes between 0.901 and 1.051, and correlations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The leaching of exchangeable bases behaves as predicted by cation exchange selectivity previously reported [17]. Phosphate is leached in very low amounts (<0.1%), even though sewage sludge and sludge ash present large P contents; this is due to the specific PO 4 adsorption, which is a characteristic of Chilean volcanic soils [12].…”
Section: Soil Attenuationmentioning
confidence: 67%
“…The leaching of exchangeable bases behaves as predicted by cation exchange selectivity previously reported [17]. Phosphate is leached in very low amounts (<0.1%), even though sewage sludge and sludge ash present large P contents; this is due to the specific PO 4 adsorption, which is a characteristic of Chilean volcanic soils [12].…”
Section: Soil Attenuationmentioning
confidence: 67%
“…One method that can eliminate compositional incoherence is to use log-ratio models as used for illite previously (Reynolds, 2015). The Rothmund-Kornfeld model is also widely applied to ion-exchange thermodynamics and is a type of log-ratio model (Bond, 1995;Bond & Verberg, 1997;Rad & Towfighi, 2020;Reynolds, 2015;Escudey et al, 2002;Yakubu & Agbenin, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They found that the Rothmund-Kornfeld model was the most effective of those available for a wide range of ions and resins. The Rothmund-Kornfeld model continues to be used extensively [23][24][25][26][27][28][29][30][31]. The Rothmund-Kornfeld model predicts the logratio of the ions in one phase from the log-ratio of the ions in another phase.…”
Section: Introductionmentioning
confidence: 98%